Osteogenic properties of manganese-doped mesoporous bioactive glass nanoparticles - Westhauser, Fabian; Wilkesmann, Sebastian; Nawaz, Qaisar; Schmitz, Sarah I.; Moghaddam-Alvandi, Arash; Boccaccini, Aldo R. (Journal of biomedical materials research, 2020)
Mesoporous bioactive glass nanoparticles (MBGNs) based on the SiO2-P2O5-CaO system have demonstrated promising properties for the local delivery of therapeutically active ions with the aim to improve their osteogenic properties.
First published: 10 April 2020
Gesehen am 07.01.2022